Protective effects of CAPE against testicular damage in streptozotocin-induced diabetic rats - Taslidere Elif; Vardi Nigar; Elbe Hulya; Taslidere Asli; Taslidere Bahadir; Cirik Hilal; Dogan Zumrut; Turkoz Yusuf (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2023)
Objective: The aim of this study was to investigate the protective effect of CAPE on oxidative stress and apoptosis against streptozotocin (STZ)-induced damage in rat testis after diabetes.  Materials and methods: The rats were randomly divided into 4 groups: Control animals, Control animals given CAPE, STZ-induced diabetic animals, and STZ-induced diabetic rats given CAPE. Diabetes was induced by a single intraperitoneal injection of STZ (55 mg/kg). Testicular damage was examined by using hematoxylin and eosin staining and apoptosis was determined by Caspase-3. Potential disorders associated with seminiferous tubular sperm formation were evaluated using the Johnsen score and seminiferous tubule diameters were measured using the Leica Q Win Plus Image Analysis System.  Results: Diabetic rats showed an increase in degenerated germ cells along with a decrease in seminiferous tubule diameter. Also, Caspase-3 positive cells were significantly increased in diabetic rats compared to control rats. On the other hand, CAPE significantly reduced the damage and germ cell apoptosis in diabetic rat testis. In testis tissues samples. CAPE treatment significantly decreased the elevated tissue malondialdehyde levels, while increasing the reduced superoxide dismutase enzyme activity.  Conclusion: These results suggest that CAPE administered intraperitoneally for 20 days to diabetic rats is a potentially beneficial agent that can be used to reduce testicular damage.